2021
DOI: 10.1128/spectrum.00590-21
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of SARS-CoV-2 Specific and Neutralizing Antibodies over Seven Months after Symptom Onset in COVID-19 Patients

Abstract: The long-term characteristics of anti-SARS-CoV-2 antibodies among COVID-19 patients remain largely unclear. Tracking the longevity of these antibodies can provide a forward-looking reference for monitoring COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 26 publications
3
35
1
Order By: Relevance
“…A previous study demonstrated that 40% of asymptomatic and 12.9% of symptomatic individuals became seronegative during a study period of 8 weeks [ 20 ]. However, in accordance with the present results, most observations showed that IgG levels against SARS-CoV-2 remained relatively stable within a three-to-five-month observation period after symptom onset [ 2 , 3 , 5 , 6 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Regular re-exposure to the virus may help sustain higher neutralizing antibody levels by stimulating memory B cells to mount a rapid and effective humoral response [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…A previous study demonstrated that 40% of asymptomatic and 12.9% of symptomatic individuals became seronegative during a study period of 8 weeks [ 20 ]. However, in accordance with the present results, most observations showed that IgG levels against SARS-CoV-2 remained relatively stable within a three-to-five-month observation period after symptom onset [ 2 , 3 , 5 , 6 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Regular re-exposure to the virus may help sustain higher neutralizing antibody levels by stimulating memory B cells to mount a rapid and effective humoral response [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our 8-month follow-up, we also reported that 76% of the patients still had detectable Neutralizing Antibodies (NAb) (1). Many studies reported short-term follow-up observations of less than 6 months (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), whereas others reported longitudinal observations, typically spanning less than 12 months post symptom onset (1,4,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Some studies reported contraction of anti-COVID humoral responses with a stronger initial decline (1,4,(23)(24)(25)27).…”
Section: Introductionmentioning
confidence: 77%
“…An important aspect of monitoring humoral responses has been having access to plasma from the same patients over 14 months. Most reports were based on cross-sectional analysis spanning less than 6 months (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) or up to 12 months (1,4,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Depending on the patient cohort, several studies reported a stronger initial contraction (1,4,(23)(24)(25)27) of anti-COVID humoral responses.…”
Section: Discussionmentioning
confidence: 99%
“…Based on serological studies of naturally infected populations, IgM antibodies are the first to be expressed and are mainly present in the circulation, promoting antigenic modulation (2,3). IgG antibodies begin to appear later in the immune response because they undergo affinity maturation through somatic mutations, resulting in high affinity for the target antigen and an enhanced ability to neutralise the pathogen (2).…”
Section: Introductionmentioning
confidence: 99%